Ecosystem services of the Guarapiranga Reservoir watershed (São Paulo, Brazil): value of water supply and implications for management strategies. Issue 1 (2nd January 2018) - de Brito, Felipo Meireles; Miraglia, Simone Georges El Khouri; Semensatto, Décio
ABSTRACT: Essential ecosystem services provided by watersheds consider quantity and quality of water supply. In the current study, we used the Avoided Cost valuation method to assess the impacts of changes in land use of Guarapiranga Reservoir watershed (Metropolitan Region of São Paulo, Southeast Brazil) on the quality of raw water and on costs of treating the public water supply. Vegetation cover area significantly correlates with the average dosage of reagents for raw water treatment. Reduction of vegetation area increased 7.1 times the cost of water treatment, generating a significant externality for users of the system that reached around US$ 6.6 million in 2010. Even whether underestimated, management of the Metropolitan reservoirs should consider this value, enabling to reinforce water conservation as a state policy and effectively implemented with the participation of society. This study highlights the potential governing processes and management strategies related to the sustainable management of the watershed.